An audit of MTP in women with high-risk pregnancy - Srivastava, Deepali; Srivastava, Sandeepa; Kumari, Pratibha; Srivastava, Deepanshi (Asian Journal of Medical Sciences, 2021)
Background: The women who have been pregnant more than four times are fewer than 18or over 35-years-old, or have at least one medical issue before or during pregnancy, the pregnancy is considered high-risk. Increased maternal and foetal mortality and morbidity are linked to these risk factors. MTP in itself is a blind and risky procedure and performing it in High Risk Pregnancy (HRP) is a challenge for obstetrics and gynecology personnel. When performed with all pre, intra and post-op precautions, results are good and patient-friendly. Aims and Objectives: Aims of the study were to calculate the number, high-risk factors, method used, and its outcome of MTP in HRP. Materials and Methods: The present study was a retrospective observational study done at QMH, KGMU, Lucknow performed on subjects admitted for MTP from January 2018 to December 2018. Total admitted patients seeking MTP were 450 out of which 93 belonged to High-Risk Group who underwent surgical and medical abortion accordingly. All precautions and norms defined by Govt. of India were taken care of. Cases were evaluated on the basis of high-risk factors- Age, parity, obstetrical and medical illnesses, and interval since last delivery. Results: Out of 93 high-risk cases, 88 cases were of 1st trimester and 5 were of 2nd trimester abortion. Six cases required suction evacuation while seven cases were managed medically using medical abortion kit. Contraception was given to all subjects according to their needs. Seventy-one women were of more than 35 yrs, while two were teenagers. 21 women were grand multipara. Women of obstetrical risk were 17 while the rest were having medical illnesses. Conclusion: This study concludes that there are a large number of high-risk groups for MTP again showing unmet need and lack of specialized counseling of HR patients according to their mental and physical condition. Early recognition of pregnancy and timely intervention can be lifesaving in these women and proper contraceptive counseling is required to prevent future pregnancies.